Expression of COA6 in breast cancer and its correlation with tumor immune cell infiltration - JIN Xiaoxia, LIU Yushan, HU Jiping, ZHU Xinghua (Jichu yixue yu linchuang)
Objective To detect the expression of cytochrome c oxidase assembly factor 6(COA6) in breast cancer, study its clinical significance, and analyze the effect of COA6 on immune infiltration in breast cancer. Methods Differential genes were screened by the whole transcriptome sequencing and the expression of COA6 was explored with TCGA(The Cancer Genome Atlas Program) database. The tissues of 125 breast cancer and adjacent tissues were stained by immunohistochemistry to detect COA6 protein expression and analyze the correlation with clinical features. The COA6 mRNA and protein expression in breast cancer cells and tissues were determined by qRT-PCR and Western blot, respectively. The TIMER(Tumor Immune Estimation Resource) database was used to analyze the correlation between high COA6 gene expression and immune cell infiltration. Results The positive expression rate of COA6 in breast cancer tissues was 88%(110/125), which was higher than that of paracarinoma tissues(7.2%, 9/125)(P＜0.05) and was positively correlated with tumor size and histological grade. In fresh breast cancer tissues, COA6 protein expression was significantly higher than that in adjacent tissues. Both COA6 mRNA and protein expression were significantly increased in the breast cancer cell lines. COA6 was positively correlated with the infiltration of helper T cells, NK cells, CD8+ T cells, M1 type macrophages, regulatory T cells, dendritic cells, and memory CD4+ T cells in the tumor microenvironment. Conclusions The expression level of COA6 is increased in breast cancer and is positively correlated with tumor immune infiltration, which provides a potential therapeutic target for breast cancer treatment.